Chinese Bridge Competition Malaysia Preliminary 2021 - Muhammad 'Arif, Mohamad (Faculty of Computing, 2021)
PEKAN, 30 August 2021 - Congratulations to FK student, Syahirah Syazwani Shamsudin for winning first place in Chinese Bridge Competition Malaysia Preliminary 2021 organized by the Chinese Embassy in collaboration with Kongzi Institute of the University of Malaya (UM).